Pelatihan Pembuatan Animasi Sebagai Alternatif Proyek Penguatan Profil Pelajar Pancasila Di Tingkat Sekolah Dasar - Malasari, Susanti; Fortinasari, Paulina Besty (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The implementation of the Pancasila values in students’ character is a challenge for teachers, due to the limited knowledge of technology and learning strategies. Animation can be used by teachers to facilitate students in creating their project-based learning which can help them to be students who internalize Pancasila values. In addition, animation is a place for teachers to explore and be creative in utilizing technology. This article discusses a training of creating animation for elementary school teachers and their perception towards the use of animation as a media of project-based learning. The stages of the training were observation, socialization, mentoring, and evaluation. The four stages were done in order to conduct the animation training activities for elementary school teachers. This training received a positive response from the participants which was marked by the participants' excitement and enthusiasm when creating animation projects. The results of this training will be used as learning media and as an alternative of students’ project-based work which is based on the demands of this modern era that is appropriate with students’ interests, students’ ways of learning, and students’ learning products.